WCO-Lite version 1.1: an online nomenclatural catalogue of harvestmen of the world (Arachnida, Opiliones) curated in TaxonWorks - Kury, Adriano B.; Mendes, Amanda C.; Cardoso, Lilian; Kury, Milena S.; Granado, Alexia A.; Yoder, Matthew J.; Kury, Ian S. (Zootaxa, 2021)
The “World Catalogue of Opiliones” (WCO) is a collaborative effort to comprehensively index the Earth’s species of harvestmen. This paper announces one component of the WCO, “WCO-Lite” a website available at https://wcolite.com/. WCO-Lite provides a graphic user interface for a second component of the WCO, “Opiliones of the World”, a database on the taxonomy of the harvestmen curated in TaxonWorks (TW). WCO-Lite interfaces include: (1) a checklist of all valid taxa of the arachnid Opiliones, exhaustive up to December 2018; (2) a taxonomic tree; (3) a search engine comprising two modules; and (4) a counter of species diversity for each taxon. An e-Book companion was launched simultaneously with WCO-Lite version 1.1 on September 12, 2020 to account for the formal publication of mandatory nomenclatural changes and availability of taxonomic names. The collective components of the WCO are also being summarized in a forthcoming conventional paper-form catalogue, currently in manuscript stage.